2014
DOI: 10.1371/journal.pone.0101557
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Significance of Leaf Epidermal Features in Holcoglossum (Orchidaceae)

Abstract: Determining the generic delimitations within Aeridinae has been a significant issue in the taxonomy of Orchidaceae, and Holcoglossum is a typical case. We investigated the phylogenetic utility of the morphological traits of leaf epidermis in the taxonomy of Holcoglossum s.l. by using light and scanning electron microscopy to analyze 38 samples representing 12 species of Holcoglossum, with five species from five closely related genera, such as Ascocentrum, Luisia, Papilionanthe, Rhynchostylis and Vanda. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Biogeographic analyses and molecular phylogeny suggest that Holcoglossum dispersed from tropical regions to the HDM and then radiated there [23]. Previous results indicated that the pendent growing pattern [23] and laterocytic and polarcytic stomata are perhaps ecological adaptations to the strong winds and ample rains in the alpine region of the HDM [26]. Rapid changes in temperature and weather conditions are major challenges for the species living in temperate alpine regions in the HDM.…”
Section: Introductionmentioning
confidence: 99%
“…Biogeographic analyses and molecular phylogeny suggest that Holcoglossum dispersed from tropical regions to the HDM and then radiated there [23]. Previous results indicated that the pendent growing pattern [23] and laterocytic and polarcytic stomata are perhaps ecological adaptations to the strong winds and ample rains in the alpine region of the HDM [26]. Rapid changes in temperature and weather conditions are major challenges for the species living in temperate alpine regions in the HDM.…”
Section: Introductionmentioning
confidence: 99%
“…Moreira et al (2013) showed the leaves of Epidendrum secundum growing in the luminous area had a relatively thick cuticle, indicating adaptation to the environment with intense solar radiation, with cuticle functions as a barrier to reduce transpiration because of the high intensity of sunlight. Fan et al (2014) demonstrated other anatomical characters showing structural adaptation in other orchids. They reported that Holcoglossum had structural adaptations to strong winds and ample rains in subalpine region of the Hengduans Mountains by having laterocytic and polarcytic stomata in their leaf epidermal layer.…”
Section: Introductionmentioning
confidence: 81%
“…This result indicates that D. subulatum had more adaptive ability to coastal habitats compared to other orchid species in Sempu Island. Other studies also showed that other orchids species have adaptive anatomical characters, such as Epidendrum secundum growing in luminous area had relatively thick cuticle (Moreira et al (2013); Holcoglossum growing in subalpine region of mountainous area possessed laterocytic and polarcytic stomata in their leaf epidermal layer showing structural adaptation to strong winds and ample rains (Fan et al 2014).…”
Section: Assessment Of the Adaptive Ability Of Four Orchid Species Tomentioning
confidence: 95%
See 1 more Smart Citation
“…Anatomical data may provide clues for phylogenetic relationships and taxonomic identifications because anatomy is usually less affected by environmental conditions than (macro)morphological characters. This promise has been fulfilled in several orchid groups (e.g., [ 13 – 17 ]), including the genus Holcoglossum from Aeridinae [ 18 ]. Possibly, anatomy may help to resolve taxonomic complexities in Cleisostoma , however, only little is known about anatomical variation in the tribe Vandeae.…”
Section: Introductionmentioning
confidence: 99%